A construção de argumentos em aulas de biologia : controvérsias em torno das vacinas - Lima, Gleice Prado (2019)
Biology classes have given little priority to the development of argumentative practices related to other practices inserted in the social instances of production, communication and evaluation of scientific knowledge. What is perceived are classes in which the educator is exposed to a series of challenges to make technological and scientific advances accessible to students, requiring the planning and development of activities that effectively contribute to transform the Biology classes into investigative environments. In this sense, the use of Investigative Teaching Sequences (SEI's) contribute to students' understanding of scientific doing, through the creation of enabling environments for the construction of knowledge and arguments from the perspective of school science. Considering this fact, we seek, in this research, to analyze the process of elaboration of arguments by students in a didactic sequence developed around the vaccine, as well as to characterize the arguments produced, in view of the recurrent pro and antivaccine movements. With this objective, an Investigative Teaching Sequence (SEI) was elaborated and applied to 18 students of the 1st Year of High School of the Application College of the Federal University of Sergipe. The SEI was developed according to the model proposed by Pedaste et al. (2015) and has as a central question: Should the use of vaccines be optional? The data were obtained through video recordings and application of questionnaires. Data analysis involved: a) segmentation of classes into episodes, b) transcripts of the students' and teachers' speeches considering the most representative episodes of the evolution of students' ideas; b) mapping of students' written answers; c) identification of discursive practices between teachers and students that favored argumentation; d) differentiation of argumentative and explanatory questions; e) categorization of explanatory questions and f) characterization of the arguments produced by students. Considering the analysis of the arguments produced by the students throughout the activities, we verified how these were becoming sophisticated, presenting contributions that scientifically substantiated the deductions or hypotheses on the vaccine theme. To analyze the students' oral and written arguments, we used the Toulmin's Standard argument (TAP). We found that most students developed arguments composed of coherent conclusions (C), anchored in empirical or theoretical data (D); some rebutters (R) to limit their conclusions and qualifiers (Q), which informed about the level of relationship between the data and the conclusions. The results show that it is of paramount importance to develop activities that promote argumentation in Biology classes.